An exploratory study on the impact of virtual second life on the Islamic worldview of higher education students - Madarsha, Kamal Basha (s.n, 2012)
The study is to explore the impact of virtual second life on the Islamic worldview of higher education students... The objectives of this study are to investigate the impact of using Second Life on religious understanding and practices among Muslim tertiary students in Malaysia, and to understand how these impacts would affect their understanding of the religion, finally whether it would affect their Aqidah and Tawhidiyah. Qualitative method is deployed in which participants are interviewed face-to-face and online. The themes and sub-themes unfold in the study are embedded within two phenomena i.e. Aqidah and Experiences couched within their Intention. This is parallel to what previous literature states that virtual user’s expectations, habits, relationships, and their values will be reshaped if they are pure virtual users and if left unguided in their exploration of the Second World. Therefore as Muslims participate in Second Life and other virtual worlds, there is a need to assess how virtual worlds fit within Islamic doctrine and practices and how these worlds can be used in ways that are beneficial to the Muslims. It is hoped that this research can contribute to the relationship of the virtual world and the Islamic worldview, thereby provide a guidelines for the appropriate online utilization of ICT so as to be in line with the Islamic teaching and the sustenance of the Aqidah.